Analisis Ketahanan Pangan di ASEAN: Pengaruh Iklim, Luas Lahan, dan Tenaga Kerja melalui Produksi Pertanian dalam Perspektif Ekonomi Islam - Rahmadewi, Riska; Fasa, Muhammad Iqbal; Verawati, Heni (Jurnal Sosial Ekonomi Pertanian, 2026)
Food security in the ASEAN region shows complex dynamics, with varying Prevalence of Undernourishment (PoU) between countries. Although many countries have shown improvement, some countries such as Indonesia and Myanmar still face challenges related to climate change, production fluctuations, and land and labor constraints. This study aims to analyze the impact of climate, land area, and labor on food security in six ASEAN countries (Laos, Thailand, Vietnam, Myanmar, Indonesia, and Philippines) during the period 2014-2023, with agricultural production as a mediating variable. The method used is quantitative with secondary data from FAOSTAT, the World Bank, and other sources, which are analyzed through a panel data regression model using Chow, Hausman, and LM tests in EViews 13. The Sobel Test is used to test the mediating effect. The results show that land area and labor have a positive and significant effect on PoU (decreasing food security) and agricultural production, while climate has a negative but insignificant effect on PoU (increasing food security) and and a positive but insignificant effect on agricultural production. Agricultural production has a negative and significant effect on PoU (increasing food security) and acts as a mediator for the effects of land area and labor. These findings emphasize the importance of fair and sustainable natural resource management, in accordance with the principles of maqashid syariah. Keywords: Food Security, Climate, Land Area, Labor, Agricultural Production, Islamic Economic